Electoral data archive 1948-1970 - Gustafsson, Göran (Lund University, 1982)
The data collection consists of data from all parliamentary elections and county council elections during the period 1948-1970. There are also information about branches of trade and occupational groups in 1950, 1960 and 1970. The municipalities covered are the ones that were created by the amalgamation reform in 1952.

Datainsamlingen består av data från samtliga riksdagsval och landstingsval under perioden 1948-1970. Det finns också information om branscher och yrkesgrupper i 1950, 1960 och 1970. De omfattade kommunerna är de som skapades av sammanslagningsreformen 1952.
Valdataarkivet 1948-1970
Keywords: elections; val; occupations; yrken; religious attendance; religiöst deltagande; voting; röstning; parliamentary elections; riksdagsval; self-employed; egenföretagare; farmers; jordbrukare; population; befolkning; population distribution; befolkningsfördelning; population dynamics; befolkningsdynamik; white collar workers; tjänstemän; workers; arbetare; agricultural workers; jordbruksarbetare; labour force; arbetsstyrka; Employment; Sysselsättning; Elections; Val; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap